Answer:
Oh Hi There!
Here’s ur answer!
These are the following steps to solve by substitution :-
1] Step One→ Solve one equation for either x or y.
2] Step Two→ Substitute the expression from step one into the 2nd equation.
3] Step Three→ Solve the second equation for the given variable.
4] Step Four→ Plug you solution back into the first equation.
5] Step Five→ Write your solution as a point.
Step-by-step explanation:
Hope it helps you :)
Keep Learning :)
Have a good day ahead :)
Answer:
B
Step-by-step explanation:
(-a^3b^2*-a^-2b^-3)^-2/2a^2b^-3
= a^4b^9/2a^8b^4
=b^5/2a^4
so your answer is b^5/2a^4
Answer:
x = 5 or x = 1
Step-by-step explanation:
x² - 6x + 7 = 0
x² - 6x = -7
x² - 6x + 9 = -7 + 9 1/2 of the x term than square it and add it the both sides.
(x - 3)(x - 3) = 2
( x -3)² = 2
= ![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
(x - 3) = ± 2
x - 3 = 2 or x - 3 = -2
x = 5 or x = 1